Prevod, priredba, prevod priredbe - Stanovnik, Majda (Primerjalna književnost, 1998)
Translation, adaptation, translated adaptation. - Translation and adaptation are common but complicated literary phenomena. Both include independent texts of the literary genres and interdependent texts of the polyartistic genres (strip, song, drama, opera, film etc.). Both can occur separately or co-exist as part translation, part adaptation of the source text. The combination is usually labelled as a modified, e.g. "free" or "dynamically equivalent" or "functional" translation; adaptation is thus only vaguely hinted at. - Nevertheless they are discernable as two different text species. Their common feature is the nature of their provenance, i.e. their unavoidable dependence of a pre-existent text, and consequently their status of a derived, secondary text. Their source text may be primary or secondary, since translation can be adapted or/and translated, and adaptions can be translated and/or adapted as well as originals. The relations of the two species to the source text, however, differ. Translation is a complete linguistic transformation of its source text, but also its close formal and conceptual reconstruction within the frame of the same literary genre or text species. Adaptation is unmistakably linked to its source text by selected elements (title, characters, story, quotations, paraphrases etc.), but has a different individual structure and frequently belongs to another genre or species. - A case of translation-adaptation interrelations is studied on samples of a primary text, its adaptation and their translations: W. Shakespeare's interdependent text of his sophisticated verse drama Romeo and Juliet (1596?) was turned by Charles Lamb into an independent text of an identically titled but simplified prose tale, sprinkled with minor Shakespearian quotations; O. Župančič translated Shakespeare's text into Slovenian (Romeo in Julija, 1940), thoroughly reconstructing its dramatic structure and verse form while frequently modifying the meaning and form of its lexemes, syntagms, claudes and sentences; I. Črnagoj (Pripovedke iz Shakespeara, 1953 and further editions) and I. Majaron (Zgodbe po Shakespearu, 1995) reconstructed Charles Lamb's narrative structure and prose style in their translations, while neglecting a number of its details and distinctions. They both correctly quoted Župančič's translated verses wherever Shakespeare's originals had been manifestly included in Charles and Mary Lamb's Tales from Shakespeare (1807), but practically ignored Župančič's version where parts of the original verses were less obviously integrated into the prose adaptation. - The adaptation's verbal correspondence to the original is stronger than that of the adaptation's translations to the translation of the original. So, all translations demonstrate the same general attitude to their source texts, regardless of their status: they follow their essentials while modifying a number of their details. They seem to prefer the position of secondary texts, even when they are actually doubly dependent, tertiary ones, e.g. when their source texts are adaptations. It may be concluded that the source text : translation relation is basically constant in spite of the translations' variability, while the xource text : adaptation relation does not follow a fixed basic pattern.
Keywords: literarna teorija; literary theory; teorija prevajanja; translation; prevajanje; priredba; prevod